Sweet potato NAC transcription factor NAC43 negatively regulates plant growth by causing leaf curling and reducing photosynthetic efficiency - Sun, Sifan; Li, Xu; Nie, Nan; Chen, Yanqi; Gao, Shaopei; Zhang, Huan; He, Shaozhen; Liu, Qingchang; Zhai, Hong (Frontiers in Plant Science, 2023)
Leaves comprise one of the most important organs for plant growth and development. Although there have been some reports on leaf development and the establishment of leaf polarity, their regulatory mechanisms are not very clear. In this study, we isolated a NAC (NAM, ATAF, and CUC) transcription factor (TF), i.e., IbNAC43, from Ipomoea trifida, which is a wild ancestor of sweet potato. This TF was highly expressed in the leaves and encoded a nuclear localization protein. The overexpression of IbNAC43 caused leaf curling and inhibited the growth and development of transgenic sweet potato plants. The chlorophyll content and photosynthetic rate in transgenic sweet potato plants were significantly lower than those in wild-type (WT) plants. Scanning electron microscopy (SEM) and paraffin sections showed that the ratio of cells in the upper and lower epidermis of the transgenic plant leaves was unbalanced; moreover, the abaxial epidermal cells were irregular and uneven in transgenic plants. In addition, the xylem of transgenic plants was more developed than that of WT plants, while their lignin and cellulose contents were significantly higher than those of WT. Quantitative real-time PCR (qRT-PCR) analysis showed that the overexpression of IbNAC43 upregulated the genes involved in leaf polarity development and lignin biosynthesis in transgenic plants. Moreover, it was found that IbNAC43 could directly activate the expression of the leaf adaxial polarity-related genes IbREV and IbAS1 by binding to their promoters. These results indicate that IbNAC43 might play a critical role in plant growth by affecting the establishment of leaf adaxial polarity. This study provides new insights regarding leaf development.